Building Systemic Resilience against Climate Variability and Extremes (ClimBeR) program: towards outcome monitoring in Morocco - Ait El Mekki, Abdelkader; Brouziyne, Youssef (International Water Management Institute (IWMI), 2024)
This report presents the monitoring approaches discussed with the Moroccan Ministry of Agriculture for outcome reporting of the policy research conducted under Work Package 4 of the CGIARs “Building Systemic Resilience against Climate Variability and Extremes (ClimBeR)” initiative in the country. Key approaches suggested for facilitating and monitoring outcomes towards climate resilience are: